Rheology of α-Gel Formed by Amino Acid-Based Surfactant with Long-Chain Alcohol Effects of Inorganic Salt Concentration - Ichihara, Kumika (Langmuir : the ACS journal of surfaces and colloids, 2021)
Mixtures of surfactants, long-chain alcohols, and water sometimes yield lamellar gels with hexagonally packed alkyl chains. This assembly is called "α-gel" or "α-form hydrated crystal." In this study, we characterized the rheological properties of α-gel prepared using disodium N-dodecanoylglutamate (C12Glu-2Na), 1-hexadecanol (C16OH), and water at different NaCl concentrations. The α-gel structure was assessed using small- and wide-angle X-ray scattering (SWAXS). The SWAXS measurements revealed that an increased NaCl concentration (0-200 mmol dm-3) resulted in a decreased d-spacing caused by the screening of electrostatic repulsion between lamellar bilayers. This led to an increased amount of excess water (i.e., the water present between the α-gel domains), and hence, the viscosity of the α-gel decreased in the range of the NaCl concentration. A further increase in the NaCl concentration (200-1000 mmol dm-3) resulted in decreased electrostatic repulsion between the α-gel domains and/or an increased number of α-gel domains (multilamellar vesicles). These effects increased the domain-to-domain interactions, leading to increased viscosity. Therefore, we concluded that the viscosity of the α-gel was controlled by the amount of excess water and the domain-to-domain interactions. Once the network structure collapsed under the strain, it was difficult to recover the original network structure. The low recoverability resulted from increased cohesion between the domains at high NaCl concentrations